Substituição de silagem de grãos úmidos de milho por polpa cítrica peletizada em dietas para ovinos - Lima, Murillo Matias (2022)
The objective of this work was to evaluate the inclusion of pelleted citrus pulp (PCP) as an energy source with potential to replace wet corn grain silage (SGUM) in total mixture in sheep feeding. The experiment was carried out at the Federal University of Grande Dourados, in the Animal Science Department of the Faculty of Agrarian Sciences, 12 uncastrated male sheep without defined breed (SRD) were used. The treatments evaluated were 1) total mixture 0: having SGUM as the main energy source, 2) total mixture 50: substituting 50% SGUM and 3) total mixture 100: replacing 100% SGUM. Animals were housed in metabolic cages to determine DM and nutrient digestibility, intake, nitrogen balance, rumen fermentation, and microbial protein synthesis. The silage of wet corn grains, by pelleted citrus pulp, caused a quadratic effect (p<0.05) in the dry matter intake, observing an increase in intake when the DM level 27% was included (1.37 kg/day of DM in the control treatment to 1.41kg/day) and showing a decrease in the level of total replacement of SGUM (total mixture 100 with 54% of PCP in DM 1.28kg/day). The NDF digestibility coefficient increased linearly with the inclusion of pelleted citrus pulp. The treatments did not cause difference in N-consumed. The efficiency in the synthesis of microbial protein was higher for the mixtures containing PCP, observed by the linear increase of N-microbial and PB-microbial (74.44 g/day of microbial protein in the total control mixture, to 98.17 g/day in the total mixture with 27% PCP in MS and to 105.33 g/day in the total mixture with 54% PCP in MS). A linear increase in ruminal pH (5.72, 5.92 and 6.32) can also be observed as the substitution of SGUM for PCP increases. It was concluded that the by-product can be used in association or substitution of SGUM in the total mixture of sheep. However, the best level of replacement was the treatment with 50% replacement of wet corn silage by pelleted citrus pulp, enabling efficient dry matter (DM) consumption.